Influence of Transition Metal Charge Compensation Species on Phase Assemblage in Zirconolite Ceramics for Pu Immobilisation. (2020) - Blackburn, L.R.; Sun, S.K.; Gardner, L.J.; Maddrell, E.R.; Stennett, M.C.; Hyatt, N.C.
ABSTRACT: Immobilisation of Pu in a zirconolite matrix (CaZrTi2 O7 ) is a viable pathway to disposition. A-site substitution, in which Pu 4+ is accommodated into the Ca 2+ site in zirconolite, coupled with sufficient trivalent M 3+ /Ti 4+ substitution (where M 3+ = Fe, Al, Cr), has been systematically evaluated using Ce 4+ as a structural analogue for Pu 4+ . A broadly similar phase assemblage of zirconolite-2M and minor perovskite was observed when targeting low levels of Ce incorporation. As the targeted Ce fraction was elevated, secondary phase formation was influenced by choice of M 3+ species. Co-incorporation of Ce/Fe resulted in the stabilisation of a minor Ce-containing perovskite phase at high wasteloading, whereas considerable phase segregation was observed for Cr 3+ incorporation. The most favourable substitution approach appeared to be achieved with the use of Al 3+, as no perovskite or free CeO2 was observed. However, high temperature treatments of Al containing specimens resulted in the formation of a secondary Ce-containing hibonite phase.